EXTERNAL OBSTETRIC ROTATION OF THE FETUS - Светлана Владимировна Шрамко; Екатерина Сергеевна Леонова; Марина Викторовна Алексеева (The Publishing House Medicine and Enlightenment, 2024)
One of the main problems of modern obstetrics is the increase in the proportion of surgical delivery. Over the past 20 years, the rate of caesarean sections has increased from 15 % to 20 %. This increase concerns the causes of causes, including the delivery of pregnant women with a pelvic position, which ranks third, which showed a caesarean section. In this regard, external obstetric rotation seems to be a resource measure to reduce the number of surgical deliveries.